La responsabilidad social de las empresas y la cultura de la certificación - José Boza Chirino (Atlantic Review of Economics, 2011)
– The European Commission, Communication from the Commission on 2.7.2002, defined CSR as the voluntary integration, by enterprises, social and environmental concerns in their operations and relationships with partners. The EU commitment to ethical management as a way to integrate the culture of corporate social responsibility. The responses of companies wasted no time in recent years have proliferated and Social Responsibility Reports and Sustainability reports. This study is an invitation to debate on social responsibility and their ability to become certified. The conclusions suggests that the socially responsability of the companies does not need to be assessed and certified as such.
Keywords: L20; 330; social responsibility; certifications; CSR reports; Corporate Social Responsibility